Enhanced Quantification for 3D Energy Dispersive Spectrometry: Going Beyond the Limitation of Large Volume of X-Ray Emission. (24th June 2014) - Burdet, Pierre; Hébert, Cécile; Cantoni, Marco
Abstract This paper presents a method developed to quantify three-dimensional energy dispersive spectrometry (3D EDS) data with voxel size smaller than the volume from which X-rays are emitted. The influence of the neighboring voxels is corrected by applying recursively a complex quantification, improving thereby the accuracy of the quantification of critically small features. The enhanced quantification method is applied to simulated and measured data. A systematic improvement is obtained compared with classical quantification, proving the concept and the prospect of this method.